Behavioral Sciences in the Optimization of Pharmacological and Non-Pharmacological Therapy for Type 2 Diabetes - Lopes, António (2021)
Type 2 diabetes mellitus is one of the main chronic diseases worldwide, with a significant impact on public health. Behavioral changes are an important step in disease prevention and management, so the way in which individuals adapt their lifestyle to new circumstances will undoubtedly be a predictor of the success of the treatments instituted, contributing to a reduction in the morbidity and mortality that may be associated with them. It is essential to prepare and educate all diabetic patients on the importance of changing behavioral patterns in relation to the disease, with health professionals assuming an extremely important role in this area, both from a pharmacological and non-pharmacological point of view, and also ensuring the monitoring of the progress of these measures. Diabetes is a chronic disease that requires a high self-management capacity on the part of patients in order to achieve success in treating the disease, and non-adherence to therapy or non-compliance with the previously defined plan, together with an erratic lifestyle, will contribute to failure in controlling the disease. The lower adherence to pharmacological and non-pharmacological treatment in diabetes is mainly correlated to socio-economic aspects, lower health literacy, the side effects associated with the use of antidiabetic therapy or even the concomitant use of several drugs. This article consists of a narrative review that aims to synthesize the findings published in the literature, retrieved by searching databases, manuals, previously published scientific articles and official texts, following the methodology of the Scale for Assessment of Narrative Review Articles (SANRA). We aim to address the importance of behavioral sciences in the treatment of diabetes, in order to assess behavior factors and barriers for behavior changes that have an impact on the therapeutic and non-therapeutic optimization in patients with type 2 diabetes mellitus control.